Karité gets organised in Burkina - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The growing karité sector in Burkina Faso is shaping itself up to maximise returns for producers, processors and traders. Among the steps underway are the provision of manual presses to groups of women producers (since the return on karité butter...